2016
DOI: 10.1371/journal.pone.0156264
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Fragmented Seagrass Canopies and the Local Hydrodynamics

Abstract: The systematic creation of gaps within canopies results in fragmentation and the architecture of fragmented canopies differs substantially from non-fragmented canopies. Canopy fragmentation leads to spatial heterogeneity in hydrodynamics and therefore heterogeneity in the sheltering of canopy communities. Identifying the level of instability due to canopy fragmentation is important for canopies in coastal areas impacted by human activities and indeed, climate change. The gap orientation relative to the wave di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 52 publications
4
21
1
Order By: Relevance
“…less resilient) and allow greater penetration of waves and currents into the canopy, which will enhance sediment resuspension and favor exchange between the meadow and the gap. These conclusions support those of , while Hendriks et al (2008), El Allaoui et al (2015 and El Allaoui et al (2016) reported the buffering of sediment resuspension by P. oceanica meadows. El Allaoui et al (2016) found that canopies with large gaps had a higher mixing level than canopies with small gaps, despite both canopies having the same total gap area.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…less resilient) and allow greater penetration of waves and currents into the canopy, which will enhance sediment resuspension and favor exchange between the meadow and the gap. These conclusions support those of , while Hendriks et al (2008), El Allaoui et al (2015 and El Allaoui et al (2016) reported the buffering of sediment resuspension by P. oceanica meadows. El Allaoui et al (2016) found that canopies with large gaps had a higher mixing level than canopies with small gaps, despite both canopies having the same total gap area.…”
Section: Discussionsupporting
confidence: 86%
“…While light climate and temperature were not measured in this study, we recognize that the change in seagrass structure among campaigns could markedly influence the observed hydrodynamic conditions in the vicinity of the seagrass bed. El Allaoui et al (2016) highlighted the increase in the mixing level that occurred in a patchy canopy compared with a canopy without gaps. An increase in mixing can cause an increase in sediment resuspension, which can result in a reduction in water clarity, threatening seagrass growth (Lawson et al 2007, van der Heide et al 2007, Carr et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites with high silt content usually have a low diversity of species, while sites with coarse sediment particles have a much richer diversity of species (Thrush et al, ). As El Allaoui et al () pointed out, the presence of edges in canopies has been found to modify the hydrodynamics of the system, presenting a behavior that is neither that of the fully vegetated or the nonimpeded cases, but rather falls between. Ricart et al () also found that edges within a canopy change the sedimentary pattern, and they point out the importance of hydrodynamics to explain sediment pattern distribution.…”
Section: Discussionmentioning
confidence: 99%
“…These gaps may have both natural and/or human origins. For example, storms directly or indirectly may erode mattes by tearing whole sections away or scouring out their sediments, while laying cables or pipes in sea canopies favors the formation of gaps and changes the hydrodynamics in the canopy (El Allaoui et al, ). The persistence of coastal wetlands depends on the sediment deposition that controls the vertical position of the salt marsh surfaces (Bell et al, ).…”
Section: Introductionmentioning
confidence: 99%